Biphenotypic acute leukemia: a report of two cases - RZ Azma; NH Hamidah; C-F Leong; Fadilah SAW; O Ainoon; Salwati S; S-K Cheong; Sharifah N A (Penerbit UKM, 2006)
We report two cases of biphenotypic acute leukaemia diagnosed in Hospital Universiti Kebangsaan Malaysia (HUKM), their clinical, haematological characteristics and response to chemotherapy. Both patients are middle-aged ladies who presented with hepatosplenomegaly and high white cell count, mainly composed of blast cells. Their bone marrow aspirations were hypercellular comprising of more than 90% heterogenous blast cells. Cytochemical analyses show more than 3% positivity towards peroxidase, with smaller blasts showing block positivity towards PAS. Immunophenotypically, the blasts showed dual expression of CD 33 and CD 19, CD 19 and CD34, intra CD22, intra TdT and intraMPO. One of the patients showed presence of the Philadelphia chromosome on cytogenetic analysis which was confirmed by Fluorecsence In Situ Hybridisation (FISH). Molecular analysis also showed presence of the BCR-ABL fusion protein. Both patients were given combination chemotherapy consisting of daunorubicin and cytosine arabinoside.However, the patient with positive Philadelphia chromosome BCR-ABL did not achieve morphological remission after induction chemotherapy. In view of the poor prognosis of this disease, both the patients were planned for upfront peripheral blood stem cell transplantation